2005
DOI: 10.1177/1363461505052667
|View full text |Cite
|
Sign up to set email alerts
|

Prostitution in Vancouver: Violence and the Colonization of First Nations Women

Abstract: We interviewed 100 women prostituting in Vancouver, Canada. We found an extremely high prevalence of lifetime violence and post-traumatic stress disorder (PTSD). Fifty-two percent of our interviewees were women from Canada's First Nations, a significant overrepresentation in prostitution compared with their representation in Vancouver generally (1.7-7%). Eighty-two percent reported a history of childhood sexual abuse, by an average of four perpetrators. Seventy-two percent reported childhood physical abuse, 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 53 publications
2
76
0
6
Order By: Relevance
“…In 2000, Save the Children Canada reported that Aboriginal youth comprise 90% of the visible sex trade in various Canadian cities (Save the Children Canada, 2000). Indeed, in a qualitative study of survival sex workers in Vancouver, Farley, Lynne, and Cotton (2005) reported that the majority of participants had experienced sexual abuse and most required treatment for post-traumatic stress disorder. Young Aboriginal people who participate in survival sex work in Canadian urban settings continue to be exposed to appalling levels of drug-related harm, predation, violence and HIV-related vulnerability Spittal et al, 2006).…”
Section: Sexual Abuse and Vulnerability To Hiv Infectionmentioning
confidence: 99%
“…In 2000, Save the Children Canada reported that Aboriginal youth comprise 90% of the visible sex trade in various Canadian cities (Save the Children Canada, 2000). Indeed, in a qualitative study of survival sex workers in Vancouver, Farley, Lynne, and Cotton (2005) reported that the majority of participants had experienced sexual abuse and most required treatment for post-traumatic stress disorder. Young Aboriginal people who participate in survival sex work in Canadian urban settings continue to be exposed to appalling levels of drug-related harm, predation, violence and HIV-related vulnerability Spittal et al, 2006).…”
Section: Sexual Abuse and Vulnerability To Hiv Infectionmentioning
confidence: 99%
“…Research has shown that childhood sexual and/or physical abuse significantly predicts engagement in sex work among selected populations, including: adult females (Bagley & Young, 1987;Farley & Cotton, 2005;Potter, Martin, & Romans, 1999;Simons & Whitbeck, 1991); men who have sex with men (Kalichman, Gore-Felton, Benotsch, Cage, & Rompa, 2004;O'Leary, Purcell, Remien, & Gomez, 2003); female adolescent populations (Bagley, 1999;Simons & Whitbeck, 1991); drug using men and women (Braitstein, Tyndall, Spittal, O'Shaughnessy, Schilder, Johnston, et al, 2003); and male/female adolescent populations (Seng, 1989). These findings are of concern given the well-known risks associated with sex work among drug-using populations, including high rates of violence and assault, homelessness, social isolation, and sexual and drug-related harms.…”
Section: Introductionmentioning
confidence: 99%
“…Many more women from the Downtown Eastside have still not been accounted for-in all, there are sixty-one unsolved cases of disappearances of women since 1982 (CBC News, 2006), most of whom were known to be drug users and sex workers. Although there are many known risks involved for both male and female sex workers such as sexually transmitted disease, transmission of blood-borne pathogens such as HIV and Hepatitis C (Medrano, Desmond, Zule, & Hatch, 1999), and potential victimization and violence (Farley & Cotton, 2005), the Vancouver tragedy underscores the most severe harms involved in sex work within heavy drug using communities.…”
Section: Introductionmentioning
confidence: 99%
“…More recent Canadian research has identified Vancouver, British Columbia; Ottawa, Ontario; and Winnipeg, Manitoba as major centers for the sexual trafficking of Aboriginal women and children (Assembly of Manitoba Chiefs, 2010;CBC News Canada, 2010;Chansonneuve, 2010;Farley, Lynne & Cotton, 2005).…”
mentioning
confidence: 99%